Drying Kinetics in Solar Drying - Guiné, Raquel (2017)
From ancient times foods such as fruit, vegetables, meat or fish were dried by direct sunlight. The use of the sun as energy source is advantageous from the economic as well as environmental points of view. However, this procedure has many disadvantages concerning the efficiency and product safety and quality. The use of greenhouses can greatly minimize these problems Inside the greenhouses the air circulates by natural convection but they can also be equipped with chimneys for air outlet, thus increasing the airflow. In other cases, the efficiency of the drying system can be increased by incorporating a solar collector system, which uses panels for an efficient collection of the sun ray’s energy. Knowledge of the drying kinetics is of great importance for modeling the drying processes and to establish appropriate operating conditions. There are hundreds of mathematical models that were developed to represent the drying kinetics of foods, being mostly empirical, or semi-empirical or alternatively based on the Fick's second law of diffusion. This chapter presents the heat and mass transfer mechanisms that regulate the drying rate, the conditions in direct and indirect solar drying, the drying curves and the mathematical modeling of the solar drying processes, with application examples in various dominions.